Ezra Pound, Italy, and the Cantos - Bacigalupo, Massimo, 1947- (Ezra Pound Center for Literature series., 2020)
"Pound spent most of his life in Italy and wrote about it incessantly in his poetry. Only by following his footsteps, acquaintances and composition processes can we make sense of and enjoy his forbidding Cantos. This study provides for the first time an account of Pound's Italian wanderings and of what they became in his work. After this study we will be able to read Pound as a guide to the places, people and books he loved, and we will share the poet traveler's joys and discoveries"--